PENERAPAN METODE PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN PEMAHAHAMAN MATA PELAJARAN SKI KELAS X - Nina Fitria; Khoirul Umam (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
MAN 5 Jombang is a madrasah which in PAI learning has its focus such as the subjects of fiqh, aqidah akhlak, qur'an hadith, and SKI. Appropriate methods in delivering material are needed sso that sthe interaction sbetween teachers sand students runs swell. Thed focus of dthis research is: 1) How are interactive learning methods implemented at MAN 5 Jombang? 2) How do interactive learning methods apply in improving the understanding of SKI subjects for class X MAN 5 Jombang students? 3) What are the supporting and inhibiting factors in implementing interactive learning methods at MAN 5 Jombang? This Researct usess a case fstudy type gof research, the research approach is a qualitative approach, the data collecting techniques used were observation, interviews and documentation. The results of this research are: 1) The application of interactive methods provides a teaching structure that involves collecting and considering students' questions which are then reflected through their curiosity and realized in the form of questions and then answered by the students themselves through investigation. 2) Implementing this method must first have appropriate structure which is; planning, implementing and evaluating learning. 3) The supporting factors for this interactive learning method are; creative and educative educators, facilities in the madrasah, and monitoring in the learning process. The inhibiting factors for this interactive learning method are; the students who are less active, boredom, and the limited time.